ANALISIS FAKTOR PEMBENTUK P-TRANSQUAL PADA LAYANAN TAKSI ONLINE DI SURABAYA - Ika Mutia Lestari; Erna Andajani; Siti Rahayu (CALYPTRA, 2018)
Online taxi are one of the most favorites because online taxi is easily the most convenient way to ride than other transportation and this is extremly important to maintain passangers satisfaction and to improve for a better service quality. Service quality can be calculated using P-Transqual with 4 dimensions: comfort dimension, tangible dimension, personnel dimension, and reliability dimension. This research aims to determine and analyze 4 dimensions as P-TRANSQUAL’s dimension, especially on online taxi services in Surabaya. This research uses quantive approach by using Confirmatory Factor Analysis (CFA) method trough IBM SPSS. The data used in this study is the primary data obtained from distribution of quetionnaires. The samples of this study were selected using non-probability sampling technique, the target population characteristics are those who have been used online taxi at least once around last six month, with minimum of age is 16. The number of samples used were 200 samples. The results of this study indicate that 4 dimension are the dimension of P-TRANSQUAL on the online taxi service in surabaya.